Elucidation of Abiotic Stress Signaling in Plants 2015
DOI: 10.1007/978-1-4939-2211-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Auxin in Abiotic Stress Responses

Abstract: Auxin is among the key growth regulators that play diverse roles in virtually all aspects of plant growth and development. Intensive investigations during the past two decades have helped in elucidation of auxin perception and signal transduction mechanisms operative in plants. In addition to its primary role in regulating plant development, several studies in recent years have provided unfl inching evidence for the involvement of auxin in abiotic stress responses. Functional genomics studies and genome-wide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 140 publications
0
29
0
Order By: Relevance
“…On the other hand, it has been reported that SA application prevents drought and salinity induced IAA degradation (Fahad and Bano, 2012;Sakhabutdinova et al, 2003;Shakirova et al, 2003), justifying the higher IAA signal detection in SA than in C leaves. Moreover, this higher detection can also be associated with IAA function as stress signaling hormone in an early stage of stress (Jain and Khurana, 2009;Sharma et al, 2015). In fact, it was reported a markedly decrease of IAA with a transient increase during the initial stage of drought (Wang et al, 2008) and heat stress (Escandón et al, 2016).…”
Section: Kl and Sa Induce Changes In Aba And Iaa Dynamicsmentioning
confidence: 89%
“…On the other hand, it has been reported that SA application prevents drought and salinity induced IAA degradation (Fahad and Bano, 2012;Sakhabutdinova et al, 2003;Shakirova et al, 2003), justifying the higher IAA signal detection in SA than in C leaves. Moreover, this higher detection can also be associated with IAA function as stress signaling hormone in an early stage of stress (Jain and Khurana, 2009;Sharma et al, 2015). In fact, it was reported a markedly decrease of IAA with a transient increase during the initial stage of drought (Wang et al, 2008) and heat stress (Escandón et al, 2016).…”
Section: Kl and Sa Induce Changes In Aba And Iaa Dynamicsmentioning
confidence: 89%
“…The hormone ABA is a known stress hormone, and its levels are altered under both environmentally and developmentally induced stresses such as abiotic stress and induction of seed dormancy, etc. In recent years, the role of auxin in both abiotic and biotic stresses has also been established (Sharma et al, 2015). Since OsFBK1 is induced under stress and is also expressed during panicle development in a stage-specific manner, it could be coregulated by both developmental and environmental cues.…”
Section: The Fbp Osfbk1 Is a Component Of An Scf E3 Ligasementioning
confidence: 99%
“…clearly showing that the process of secondary cell wall thickenings of the roots is affected in the transgenics. However, as auxin concentration increased, the OsFBK1 OE plants also started accumulating more lignin than in normal conditions, possibly as a response to the increasing inhibitory action of auxin against root growth (Sharma et al, 2015), and the activation of the other CCR genes already present in the plant's repository to carry out secondary cell wall development for stress alleviation. Further, a question remains whether the changes in lignification in the transgenic lines reflect some indirect effect of altered auxin levels/signaling.…”
mentioning
confidence: 99%
“…As envisaged by De Smet et al ( 2010 ), the existence of an auxin biosynthesis, signaling, and transport apparatus in single-celled green algae indicates the evolutionary role played by auxin during adaptation of plants to diverse land environments. Through recent research, it is evident that auxin also plays a role as an integral part of plant responses to unfavorable and stressful conditions (Sharma et al 2015 ).…”
Section: Genetic Engineering Of Auxin Metabolismmentioning
confidence: 99%